Enhancing students' academic achievement in computer studies through the use of reinforcement strategy - John Bosco O.C. Okekeokosisi; Kate Chinwe Okoh (Social Sciences and Education Research Review)
The study investigated on academic achievement of secondary school computer studies students taught using reinforcement and those taught without reinforcement. The study was carried out in Nnewi North Local Government Area (NNLGA) of Anambra State, Nigeria. The study adopted pre-test post-test non-equivalent control group design. Two research questions and two null hypotheses guided the study. The study comprised of all senior secondary school II (SS2) students from Nnewi North Local Government Area (NNLGA) of Anambra State, numbering one thousand two hundred and ten (1,210). The sample size of the study was one hundred and thirty nine (139) computer studies students. Purposive sampling technique was used to select only two (2) public secondary schools out of eight (8) offering computer studies in external examination in NNLGA of Anambra State. The researchers made use of intact classes from the two groups. The validated instrument tagged "Computer Operations Achievement Test" (COPAT) was used for the data collection. Kuder Richardson Formula 20 (KR) reliability coefficient of 0.72 was established. Data collected were analyzed using mean, standard deviation and ANCOVA at 0.05 level of significance. The findings from the study revealed that reinforcement in form of praise, encouragement, motivation and hope was used as reinforcement strategy in classroom teaching. This made students taught computer operations as a topic in computer studies using reinforcement strategy (RS) performed significantly higher than the students taught computer operations as a topic in computer studies without using reinforcement strategy (RS). The study further revealed that there is no gender effect on computer studies students taught computer operation using RS. Based on the findings, the researchers recommended among others that teacher at all levels should adopt the use of reinforcement in instructional process since it helps to improve academic achievement of students in computer studies in both internal and external examination.